The Importance of the Entrepreneur’s Perception of “Success” - Esther Hormiga PÉREZ; Rosa M. Batista CANINO (Revista de Management Comparat International)
Purpose - In spite of the fact that the success of new ventures has been a widely studied topic in the field of entrepreneurship, no consensus on what is understood by the success of a firm can be found in the literature. Thus, the objective of this work is to discover what the entrepreneur really understands by the success of his/her business in its early years. To that end, this study clarifies the principal indicators used by entrepreneurs and analyses the relationship between how entrepreneurs understand the success of their business and the performance of that business. Design/methodology/approach – In a logit regression model, the research data are analyzed, using a sample of 98 entrepreneurs who are the heads of new firms in various sectors of activity. Findings - The study shows that there is a relationship between the way in which the entrepreneur measures how the business is doing and the performance of that business. More specifically, this research reveals that it is not the use of a greater number of indicators to measure the success that identifies the successful newly-created business from the unsuccessful, but the fact that those indicators are from different perspectives. Moreover, the results show that customer-related indicators are more effective than financial indicators to distinguish between successful and unsuccessful organizations. Research limitations/implications – Future research including qualitative interviews will help to further investigate the relationship between the entrepreneur’s perception of success and company performance. Practical implications – As a result of this research, the entrepreneurs can be conscience about how important it is the way they understand “the success” before they constitute their business. The results of this study mean a valuable knowledge to the academics that research in the entrepreneurship field, specifically to those that are focused on the success factors study. Originality/value – This research is pioneering in relating the way that the entrepreneur measures his company’s success and demonstrating its importance.